MOBSTER – II. Identification of rotationally variable A stars observed with TESS in sectors 1–4. Issue 4 (20th June 2019) - Sikora, J; David-Uraz, A; Chowdhury, S; Bowman, D M; Wade, G A; Khalack, V; Kobzar, O; Kochukhov, O; Neiner, C; Paunzen, E
ABSTRACT: Recently, high-precision optical 2-min cadence light curves obtained with TESS for targets located in the mission's defined first four sectors have been released. The majority of these high-cadence and high-precision measurements currently span ${\sim }28\, {\rm d}$, thereby allowing periodic variability occurring on time-scales ${\lesssim }14\, {\rm d}$ to potentially be detected. Magnetic chemically peculiar (mCP) A-type stars are well known to exhibit rotationally modulated photometric variability that is produced by inhomogeneous chemical abundance distributions in their atmospheres. While mCP stars typically exhibit rotation periods that are significantly longer than those of non-mCP stars, both populations exhibit typical periods ${\lesssim }10\, {\rm d}$ ; therefore, the early TESS releases are suitable for searching for rotational modulation of the light curves of both mCP and non-mCP stars. We present the results of our search for A-type stars that exhibit variability in their TESS light curves that is consistent with rotational modulation based on the first two data releases obtained from sectors 1 to 4. Our search yielded 134 high-probability candidate rotational variables – 60 of which have not been previously reported. Approximately half of these stars are identified in the literature as Ap (mCP) stars. Comparisons between the subsample of high-probability candidate rotationally variable Ap stars and the subsample of stars that are not identified as Ap reveal that the latter subsample exhibits statistically (i) shorter rotation periods and (ii) significantly lower photometric amplitudes.